Pengaruh Kualitas Pelayanan Kesehatan Terhadap Kepuasan Pasien Peserta BPJS di Rumah Sakit Tingkat II Udayana Denpasar - Dewantari Putri, Ayut; Dewi Pascarani, Ni Nyoman; Dwi Wismayanti, Kadek Wiwin (CITIZEN CHARTER, 2016)
ABSTRACT Through the National Health Insurance program by BPJS (Badan Penyelenggara Jaminan Sosial), it is expected that access to health care is open for everyone, so that everyone deserves quality health care. Level II Udayana Hospital was originally a hospital serving members of the army, civil servants and their families while the general public only served as minor users. Then the number of patients has increased after the hospital became a BPJS-partner hospital. The aim of this study was to obtain empirical evidence about the effect of the quality of health care on the satisfaction BPJS patient participants in the Level II Udayana Hospital. This research was done by using non-probability sampling and purposive sampling methods. The data collection was done by providing an open questionnaire to a sample of 100 respondents from BPJS inpatients participants at the Level II Udayana Hospital. Indicators in the study were tested using validity and reliability tests. The testing of the hypothesis used multiple linear regression analysis. The results showed that the quality of services which included tangible, empathy, reliability, responsiveness and assurance simultaneously and partially had an effect on patient satisfaction, with the regression equation Y = 1.372 + 0.135 X1 + 0.148 X2 X3 + 0.213 + 0.132 + 0.132 X4 X5. The results of R Square of 0.780 indicated that patient satisfaction was influenced by the quality of service by 78%, while the remaining 22% was explained by other variables not included in this study. Keywords: BPJS, Health Services, Quality of Service